COMMUNICATIVE ACTIVITIES OF TEACHING SPEAKING FOR THE STUDENTS - DENI ASRIDA (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2014)
The main objective of learning English is using English as a means of communication. One of the ways for the teachers to make the students use English as a means of communicationis using appropriate techniques which match with the learners’ characteristics in teaching speaking. Unfortunately, the fact shows that many teachers still do not know the appropriate techniques to teach speaking for the students. They frequently teach speaking using translation and memorizing techniques, whereas, those techniques are not appropriate with the characteristics of young learners. In this case, the teachers have to know the applicable techniques for teaching speaking to the students to achieve the main objective of teaching English. Thus, this article will explainsome of communicative activities which can be used by the teachers in teaching speaking.Key words: communicative, activities, speaking